Reconstruction of maxillary palatal defects after partial maxillectomy using a pedicled buccal fat pad and a nasolabial flap - Nishikubo, Shuichi (Clin Case Rep, 2021)
The novelty of this procedure is the reconstruction of a maxillary palatal defect with two pedicled flaps: a pedicled buccal fat pad and a nasolabial flap. This use of combination flaps makes the surgery simple, short, and useful for a wide defect.The novelty of this procedure is the reconstruction of a maxillary palatal defect with two pedicled flaps: a pedicled buccal fat pad and a nasolabial flap. This use of combination flaps makes the surgery simple, short, and useful for a wide defect.